Cost of integrated chronic care for severe non-communicable diseases at district hospitals in rural Rwanda - Joseph Mucumbitsi; Lauren Anne Eberly; Christian Rusangwa; Loise Ng'ang'a; Claire C Neal; Jean Paul Mukundiyukuri; Egide Mpanusingo; Jean Claude Mungunga; Hamissy Habineza; Todd Anderson; Gedeon Ngoga; Symaque Dusabeyezu; et al. (BMJ Global Health)
Background Integrated clinical strategies to address non-communicable disease (NCDs) in sub-Saharan Africa have largely been directed to prevention and treatment of common conditions at primary health centres. This study examines the cost of organising integrated nurse-driven, physician-supervised chronic care for more severe NCDs at an outpatient specialty clinic associated with a district hospital in rural Rwanda. Conditions addressed included type 1 and type 2 diabetes, chronic respiratory disease, heart failure and rheumatic heart disease.Methods A retrospective costing analysis was conducted from the facility perspective using data from administrative sources and the electronic medical record systems of Butaro District Hospital in rural Rwanda. We determined initial start-up and annual operating financial cost of the Butaro district advanced NCD clinic for the fiscal year 2013–2014. Per-patient annual cost by disease category was determined.Results A total of US$47 976 in fixed start-up costs was necessary to establish a new advanced NCD clinic serving a population of approximately 300 000 people (US$0.16 per capita). The additional annual operating cost for this clinic was US$68 975 (US$0.23 per capita) to manage a 632-patient cohort and provide training, supervision and mentorship to primary health centres. Labour comprised 54% of total cost, followed by medications at 17%. Diabetes mellitus had the highest annual cost per patient (US$151), followed by heart failure (US$104), driven primarily by medication therapy and laboratory testing.Conclusions This is the first study to evaluate the costs of integrated, decentralised chronic care for some severe NCDs in rural sub-Saharan Africa. The findings show that these services may be affordable to governments even in the most constrained health systems.